2019
DOI: 10.1108/imds-04-2018-0164
|View full text |Cite
|
Sign up to set email alerts
|

Modelling wholesale distribution operations: an artificial intelligence framework

Abstract: Purpose The purpose of this paper is to propose an artificial intelligence-based framework to support decision making in wholesale distribution, with the aim to limit wholesaler out-of-stocks (OOSs) by jointly formulating price policies and forecasting retailer’s demand. Design/methodology/approach The framework is based on the cascade implementation of two artificial neural networks (ANNs) connected in series. The first ANN is used to derive the selling price of the products offered by the wholesaler. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 58 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Moreover, Klumpp ( 2018 ) demonstrated that AI-driven SCI, such as self-driving systems, have great potential to positively stimulate the performance of logistics and transportation functions in the supply chain. Bottani et al ( 2019 ) implemented an AI-based framework to support decision-making in wholesale distribution. Accordingly, the authors claimed the potential to decrease economic loss due to out-of-stock occurrences by more than 56%.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, Klumpp ( 2018 ) demonstrated that AI-driven SCI, such as self-driving systems, have great potential to positively stimulate the performance of logistics and transportation functions in the supply chain. Bottani et al ( 2019 ) implemented an AI-based framework to support decision-making in wholesale distribution. Accordingly, the authors claimed the potential to decrease economic loss due to out-of-stock occurrences by more than 56%.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Fear is a natural and comprehensible response of humans. Fear about the unknown is human’s ancient and powerful emotion ( Bottani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fear is a natural and comprehensible response of humans. Fear about the unknown is human's ancient and powerful emotion (Bottani et al, 2019). For a quick understanding, the fear can circulate distance between the job and employees to get the salary.…”
Section: What Is the Connection Between Operational Excellence And Artificialmentioning
confidence: 99%
“…MSMEs can obtain business information on which decisions can be taken quickly. Research Bottani et al (2019) found the application of ANN (Artificial Neural Networks) has the potential to reduce economic losses due to out of stock up to 56 percent for wholesale distribution companies. AI's contributions to business activities are reducing losses, cost efficiency and accuracy of business decisions.…”
Section: The Integration Model Of Rbv and Artificial Intelligencementioning
confidence: 99%